The (re) invention interfaces of undergraduate teaching in nursing in time of COVID-19 (Research, Society and Development, 2020)
The present study aimed to socialize the experience of a group of academics and nursing professors about the transition from face-to-face study to distance learning in times of COVID-19 pandemic. This is an account of the experience of academics and professors from different periods of undergraduate nursing, in a private higher education institution, located in the West of the State of Rio de Janeiro, from March to April 2020. The experience lived in these pandemic times corroborates that, no matter how much information and communication technologies we have, none of them has the power to replace the teacher's presence in the classroom. In addition, teaching-learning in the areas of health sciences involves and requires a diversity of complex factors inherent to the teaching process. In the area of nursing, this is proven mainly by the dichotomy between face-to-face and distance learning, which highlights the central pillar for our propositions. Thus, when understanding that this complexity is composed of innumerable factors, we must direct our efforts towards academic, personal and institutional particularities, in order to detect critical nodes that prevent the advance or integration of contents, and the development of teaching skills undergraduate nursing courses.